STUDI KASUS PEMBELAJARAN MIPA BILINGUAL DI TIGA SMA RSBI DI JAWA TENGAH - Gusti Astika; Anton Wahyana (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to describe the English language used by science teachers in SMARSBI in Central Java in their bilingual classes in terms of its proportion to Indonesian,grammaticalness, and complexity. It used a descriptive method and the data were collectedthrough direct observations of eight science classes and interviews with the science teachers and the school principals. The teacher talk and interview sessions were audio recorded, transcribed, and analysed qualitatively to provide answers to the research questions. The results indicate that the science teachers at the schools did not have sufficient mastery of English for bilingual classes, which affected the students’ attitudes to the bilingual program. The interviews with the teachers and school principals also revealed problems with teachers’ motivation to improve their English in spite of the supports provided by the school management.